Intention to adopt wasiyyah among muslims community in Perlis - Nur Atiqah, Alias (2020)
As there are huge volume of unclaimed inheritance over the years, this study aims to examine the relationship between knowledge, religiosity, institutional factor, Islamic financial literacy and intention to adopt wasiyyah among Muslims community in Perlis. The novelty of this study is to investigate whether there is any difference between demographic factors and intention to adopt wasiyyah. Quantitative research design is choose in this study where questionnaire used as the main tools for data collection. The sample study contains 100 respondents and the data is analysed using SPSS version 25 and Smart Partial Squares (PLS) method version 3.0.The study found that the factors namely institutional factor and Islamic financial literacy have significant impact on the intention to adopt wasiyyah among Muslims community in Perlis. Meanwhile, for knowledge and religiosity are insignificant. Further, there is no significant difference between demographic factor and intention to adopt wasiyyah. The results support the Theory of Reasoned Action (TRA). The results contribute to new knowledge on the factor impact the intention of wasiyyah adoption in Perlis. This finding also suggested that related bodies should implement or develop more effective approach in order to promote wasiyyah adoption among Muslims in Perlis.